2022
DOI: 10.1371/journal.pone.0277416
|View full text |Cite
|
Sign up to set email alerts
|

Technological infrastructure, sleep, and rest-activity patterns in a Kaqchikel Maya community

Abstract: Sleep duration, quality, and rest-activity pattern—a measure for inferring circadian rhythm—are influenced by multiple factors including access to electricity. Recent findings suggest that the safety and comfort afforded by technology may improve sleep but negatively impact rest-activity stability. According to the circadian entrainment hypothesis, increased access to electric lighting should lead to weaker and less uniform circadian rhythms, measured by stability of rest-activity patterns. Here, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The results of the current study are in contrast to these findings, as sleep disruption is greater in nonindustrial populations, with greater time spent awake during the night. These findings are consistent with previous results from nonindustrial populations that have reported lower efficiency and/or shorter sleep duration compared to industrial populations [ 9 , 42 , 43 ]. Overall, our results suggest that the relationship between industrialization and sleep is complex, but that some aspects of technological infrastructure in industrial populations may facilitate feelings of safety that lead to better sleep.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study are in contrast to these findings, as sleep disruption is greater in nonindustrial populations, with greater time spent awake during the night. These findings are consistent with previous results from nonindustrial populations that have reported lower efficiency and/or shorter sleep duration compared to industrial populations [ 9 , 42 , 43 ]. Overall, our results suggest that the relationship between industrialization and sleep is complex, but that some aspects of technological infrastructure in industrial populations may facilitate feelings of safety that lead to better sleep.…”
Section: Discussionsupporting
confidence: 93%